Circular economy indicators: What do they measure? - Moraga, Gustavo; Huysveld, Sophie; Mathieux, Fabrice; Blengini, Gian Andrea; Alaerts, Luc; Van Acker, Karel; de Meester, Steven; Dewulf, Jo (Resources, conservation and recycling, 2019)
•Indicators are useful to support circular economy progress.•Circular economy has different definitions entailing challenges for indicators.•A classification framework to understand what indicators measure is proposed.•Most of the analysed indicators focus on the preservation of materials.•None of the analysed indicators focuses on the preservation of functions. Circular Economy (CE) is a growing topic, especially in the European Union, that promotes the responsible and cyclical use of resources possibly contributing to sustainable development. CE is an umbrella concept incorporating different meanings. Despite the unclear concept, CE is turned into defined action plans supported by specific indicators. To understand what indicators used in CE measure specifically, we propose a classification framework to categorise indicators according to reasoning on what (CE strategies) and how (measurement scope). Despite different types, CE strategies can be grouped according to their attempt to preserve functions, products, components, materials, or embodied energy; additionally, indicators can measure the linear economy as a reference scenario. The measurement scope shows how indicators account for technological cycles with or without a Life Cycle Thinking (LCT) approach; or their effects on environmental, social, or economic dimensions. To illustrate the classification framework, we selected quantitative micro scale indicators from literature and macro scale indicators from the European Union ‘CE monitoring framework’. The framework illustration shows that most of the indicators focus on the preservation of materials, with strategies such as recycling. However, micro scale indicators can also focus on other CE strategies considering LCT approach, while the European indicators mostly account for materials often without taking LCT into account. Furthermore, none of the available indicators can assess the preservation of functions instead of products, with strategies such as sharing platforms, schemes for product redundancy, or multifunctionality. Finally, the framework illustration suggests that a set of indicators should be used to assess CE instead of a single indicator.